Pedagogic Register: An Analysis of Online Classroom Interaction During Covid-19 Pandemic - Dewi, Winda Herdisa; Damayanti, Ika Lestari (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
The current pandemic has changed all aspects of life, including education. Some of the changes are the time and place of teaching due to the pandemic forcing the teaching and learning process to shift to online platforms (Zhao, 2021). As a result of these changes, the interaction between teachers and students in a classroom is also affected. By employing descriptive qualitative design, this research focused on analyzing classroom interaction in an online classroom during COVID-19 pandemic. The data were collected through observation. To analyze the data, David Rose’s pedagogic register analysis (2014, 2018) was employed. The findings showed that online classroom interaction revealed the relation between teacher efficacy and students’ positive attitudes. Then, it also showed that 21st-century skills impacted teacher’s adaption of teaching materials. Last, online classroom interaction also showed the consistency of teacher roles both in offline and online classes.